Influence of light and temperature cycles on the expression of circadian clock genes in the mussel Mytilus edulis. (July 2020) - Chapman, Emma C.; Bonsor, Brodie J.; Parsons, Daniel R.; Rotchell, Jeanette M.
Abstract: Clock genes and environmental cues regulate essential biological rhythms. The blue mussel, Mytilus edulis, is an ecologically and economically important intertidal bivalve undergoing seasonal reproductive rhythms. We previously identified seasonal expression differences in M. edulis clock genes. Herein, the effects of light/dark cycles, constant darkness, and daily temperature cycles on the circadian expression patterns of such genes are characterised. Clock genes Clk, Cry1, ROR/HR3, Per and Rev-erb / NR1D1, and Timeout -like, show significant mRNA expression variation, persisting in darkness indicating endogenous control. Rhythmic expression was apparent under diurnal temperature cycles in darkness for all except Rev-erb . Temperature cycles induced a significant expression difference in the non-circadian clock-associated gene aaNAT . Furthermore, Suppression Subtractive Hybridisation (SSH) was used to identify seasonal genes with potential links to molecular clock function and revealed numerous genes meriting further investigation. Understanding the relationship between environmental cues and molecular clocks is crucial in predicting the outcomes of environmental change on fundamental rhythmic processes. Graphical abstract: Image 1 Highlights: Novel clock gene sequences are isolated from the blue mussel Mytilus edulis . Circadian activity of eight clock and clock-associated genes are investigated. Daily variation in clock gene expression in LD and DD indicates endogenous control. Temperature cycles modulate expression pattern of a core clock gene. Candidate genes for the putative provision of seasonal information are identified.